CARBON TRADING: AN EFFECTIVE WAY TO MANAGE NATURAL RESOURCES BASED ON LOCAL WISDOM - Fahreza Setiawan, Rahmad; Akbar, Wahyu; Sofiani, Eka; Mu’in, Miftahul (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This article discusses the potential for local wisdom-based carbon trading in Central Kalimantan, highlighting CO2 emissions as the main cause of global warming triggered by human and industrial activities. High levels of CO2 emissions in Indonesia, including in Central Kalimantan, have led to increased air pollution and serious health impacts. Sustainable industrial activities without prevention or reduction efforts risk causing disasters for humans and the earth. Industrial development as a major contributor to CO2 emissions requires mitigation solutions that integrate the local wisdom of the Dayak people. Uses a descriptive-qualitative method with a literature approach involving books, journals, and articles related to carbon trading and local culture in Central Kalimantan. The integration of the carbon market with the local wisdom of the Dayak people has great potential for sustainable development in Central Kalimantan. This article highlights the role of the carbon market in reducing greenhouse gas emissions through the use of forests as carbon sinks and shows that carbon trading can improve the economic welfare of forest communities and preserve biodiversity and local knowledge. By integrating the carbon market and local wisdom, Central Kalimantan has the potential to become a major center for CO2 emission reduction and community welfare improvement. This collaboration will provide economic benefits and serve as a step toward nature conservation, particularly forests, by empowering surrounding communities. This activity will be examined from an Islamic economic perspective to assess its suitability and positive impact, while also encouraging forest conservation through community empowerment and the financial benefits generated.